Experimental and numerical investigation on diffusion-absorption refrigeration system using low GWP refrigerant R600, C9H20 and helium - R. Garma; N. Ben-Ezzine; A. Bellagi (International Journal of Thermofluids)
This paper presents the results of experimental and theoretical study of a diffusion absorption refrigerator using an original working fluid system constituted of R600 as refrigerant with low global warming potential, hydrocarbon n-nonane as absorbent and helium as auxiliary gas. The experimental prototype built and equipped with the necessary metrological sensors is connected to a computer to follow the measurements from start-up to steady state.With an adjustable heating system, the motive heat input to the generator can be varied, thus making it possible to study its effect on the performance of the refrigerator and to determine the minimum energy requirements to start cold production. Experimental results show that the temperature at the evaporator reaches -10 °C when the applied heat increases the generator temperature to 140 °C. The heat flow allowing optimal operation of the bubble pump is also determined.The collected experimental data is used to validate a developed HYSYS simulation model of the refrigerator. Simulations are then run to highlight the effect of different operating parameters on machine performance.